Underwriter Certification and Japanese Seasoned Equity Issues - Cooney, John W.; Kato, Hideaki Kiyoshi; Schallheim, James S. (Review of Financial Studies, 2003)
In sharp contrast to results in the United States, the average stock price response to an announcement of a seasoned equity issue in Japan is positive. Offer prices in Japan, unlike the United States, are announced several days before the beginning of the subscription period and incorporate a substantial discount. We suggest that the positive announcement effects in Japan are consistent with the underwriter's certification of the issuing firm's value. We characterize the underwriter's risk as a put option and find a positive association between the underwriter's risk and the announcement returns, as well as other results consistent with underwriter certification. Copyright 2003, Oxford University Press.